Breaking Borders: How Barriers to Global Mobility Hinder International Partnerships in Academic Medicine. (27th July 2021) - Wondimagegn, Dawit; Ragab, Lamis; Yifter, Helen; Wassim, Monica; Rashid, Mohammed A.; Whitehead, Cynthia R.; Gill, Deborah; Soklaridis, Sophie
Abstract : This article describes the authors' personal experiences of collaborating across international borders in academic research. International collaboration in academic medicine is one of the most important ways by which research and innovation develop globally. However, the intersections among colonialism, academic medicine, and global health research have created a neocolonial narrative that perpetuates inequalities in global health partnerships. The authors critically examine the visa process as an example of a racist practice to show how the challenges of blocked mobility increase inequality and thwart research endeavors. Visas are used to limit mobility across certain borders, and this limitation hinders international collaborations in academic medicine. The authors discuss the concept of social closure and how limits to global mobility for scholars from low- and middle-income countries perpetuate a cycle of dependence on scholars who have virtually barrier-free global mobility—these scholars being mainly from high-income countries. Given the current sociopolitical milieu of increasing border controls and fears of illegal immigration, the authors' experiences expose what is at stake for academic medicine when the political sphere, focused on tightening border security, and the medical realm, striving to build international research collaborations, intersect. Creating more equitable global partnerships in research requires a shift from the current paradigm that dominates most international partnerships and causes injury to African scholars.